1994
DOI: 10.1111/j.1699-0463.1994.tb05234.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐CD4 monoclonal antibody treatment in combination with total lymphoid irradiation and cyclosporin A in hamster‐to‐rat cardiac transplantation

Abstract: Significantly prolonged graft survival (GS) of hamster hearts transplanted heterotopically into rats can be achieved by different immunosuppressive treatment strategies. The exact mechanism of graft rejection is unclear, but it seems to be a primarily humoral, antibody‐mediated type of rejection. The histopathology of long‐term surviving grafts is controversial and the morphology of lymphoid tissue in spleens and lymph nodes as the possible site of anti‐donor antibody formation has not previously been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They showed an increase in xenograft survival from their control group (4 ± 0.9 days) for recipients prepared with TLI (9.4 ± 4.4 days, P < 0.02) or TLI + cyclosporine (19.3 ± 7.4 days, P ‫ס‬ 0.002) [73]. They later reported that graft survival time was significantly prolonged by TLI + cyclosporine + anti-CD4 monoclonal antibodies (> 34 days, P < 0.02) [74].…”
Section: Rodent-to-rodent Transplantationmentioning
confidence: 93%
“…They showed an increase in xenograft survival from their control group (4 ± 0.9 days) for recipients prepared with TLI (9.4 ± 4.4 days, P < 0.02) or TLI + cyclosporine (19.3 ± 7.4 days, P ‫ס‬ 0.002) [73]. They later reported that graft survival time was significantly prolonged by TLI + cyclosporine + anti-CD4 monoclonal antibodies (> 34 days, P < 0.02) [74].…”
Section: Rodent-to-rodent Transplantationmentioning
confidence: 93%
“…A research team from Denmark repeated the Duke experiments involving hamster‐to‐rat xenotransplantation. They showed an increase in xenograft survival from their control group (4 ± 0.9 days) for recipients prepared with TLI (9.4 ± 4.4 days, P < 0.02) or TLI + cyclosporine (19.3 ± 7.4 days, P = 0.002) [73]. They later reported that graft survival time was significantly prolonged by TLI + cyclosporine + anti‐CD4 monoclonal antibodies (> 34 days, P < 0.02) [74].…”
Section: Tli For Xenotransplantation In Animal Modelsmentioning
confidence: 99%